Hubungan antara Cara Belajar dan Kecemasan Matematika dengan Prestasi Belajar Peserta Didik Selama Pandemi Covid-19 - Rahmayanti; Andi Kusumayanti; Ulfiani Rahman (Department of Mathematics Education, 2022)
This research is a type of correlational research that aims to describe the relationship between learning methods, mathematical anxiety and learning achievement during the Covid-19 pandemic. This research approach is quantitative with descriptive analysis research methods and inferential analysis. The data analysis technique used is pearson correlation with a significance level of 5%. The instrument used in this study was in the form of an instrument in the form of a questionnaire of student statements related to learning methods and mathematical anxiety, while learning achievement data was obtained from mathematics school test scores. The population in this study was all students of class XII SMA Negeri 9 Takalar for the 2021/2022 academic year, totaling 61 students. The results of this study showed that: (1) the learning method of the majority of students at moderate intervals of 60.00-67.00 as many as 21 students with compulsive frequency (34%), mathematical anxiety of the majority of students at medium intervals of 42.00-50.00 as many as 24 learners with compulsive frequency (39%). (2) there is a significant relationship between the way of learning and the learning achievement of students which shows a correlation coefficient value of 0.638 and p < 0.05. (3) there was a significant association between mathematical anxiety and learning achievement showing a correlation coefficient value of −0.314 and p < 0.05. (4) there is a significant relationship between learning and mathematical anxiety with student learning achievement during the Covid-19 pandemic which is indicated by a correlation coefficient value of 0.676 and p < 0.05 with a positive correlation direction. It can be concluded that if the higher the way of learning and the lower the mathematical anxiety, it will produce high student learning achievement, on the contrary, if the lower the way of learning and the higher the mathematical anxiety, it will produce less / low learning achievement.